2008
DOI: 10.1073/pnas.0710530105
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous conformational change and toxin binding in α7 acetylcholine receptor: Insight into channel activation and inhibition

Abstract: Nicotinic AChRs (nAChRs) represent a paradigm for ligand-gated ion channels. Despite intensive studies over many years, our understanding of the mechanisms of activation and inhibition for nAChRs is still incomplete. Here, we present molecular dynamics (MD) simulations of the ␣7 nAChR ligand-binding domain, both in apo form and in ␣-Cobratoxin-bound form, starting from the respective homology models built on crystal structures of the acetylcholine-binding protein. The toxin-bound form was relatively stable, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
37
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 46 publications
(77 reference statements)
11
37
0
Order By: Relevance
“…Importantly, in the population that putatively becomes favored at low pH, the Trp-41 indole rings are oriented to open the channel pore. The shift in population by the binding of a ligand, a proton in the present case, is similar to what is suggested for a ligand-gated ion channel (38).…”
Section: Conformational Ensemble Of Apo Form At Low Phsupporting
confidence: 87%
“…Importantly, in the population that putatively becomes favored at low pH, the Trp-41 indole rings are oriented to open the channel pore. The shift in population by the binding of a ligand, a proton in the present case, is similar to what is suggested for a ligand-gated ion channel (38).…”
Section: Conformational Ensemble Of Apo Form At Low Phsupporting
confidence: 87%
“…A similar overall conformational change in the LBD as found upon comparison of the ELIC and GLIC structures was found in molecular dynamic simulations of a homology model of the human α7 LBD [164] . Remarkably this change is not observed in the transition from the unoccupied to the ligand-bound AChBP, which stays relatively rigid except for the movements of the C-loop.…”
Section: Ligand Binding and Conformational Changes In The Lbdsupporting
confidence: 71%
“…An alternative model is based on accessibility studies and electrophysiological recordings and denies any rotation of the helices [82] . This model proposes a tilt of the pore forming helices away from the channel axis in the intracellular end of the channel [68,164] , which removes the constriction at the intracellular end of the pore.…”
Section: Pore Shape and Gatingmentioning
confidence: 99%
“…Computational studies of pLGICs based on Normal Mode analysis (22,23) and Molecular Dynamics (24,33) have demonstrated that global twisting is encoded in the structural topology of these ion channels and have suggested a role for this quaternary change in the gating process. These findings were refined by the structural studies at high resolution of GLIC, ELIC, and GluCl, which demonstrated that, in addition to quaternary twisting, substantial tertiary changes in the TM domain determine the opening/closing of the ion pore (14)(15)(16)18).…”
Section: Resultsmentioning
confidence: 99%